El ciclo de Kolb y su incidencia en los procesos de enseñanza en las clases de educación física, Loja, 2023. - Salazar Alvarez, Patricio Fernando (2023)
The present work of curricular integration had the objective of determining the incidence of the Kolb cycle applied to the teaching process in 8th grade students of General Basic Education in physical education classes at the Adolfo Valarezo High School in the city of Loja; it was a mixed correlational and descriptive study, with a quasi-experimental design. The pre-application was carried out based on Kolb's cycle to 28 eighth grade students, obtaining as initial result that students in the experience phase with 89%, reflection 82%, conceptualization 89% and application with 64% were all in an insufficient indicator, presenting difficulties in the different phases of Kolb's cycle learning, evidencing these results, we proceeded to apply the pedagogical proposal using the ERCA cycle structured for a total of 12 classes with four weekly pedagogical hours, the purpose of which was to enhance the students' learning and thus improve the teaching process. Consequently, after the application of the proposal, the results obtained improved, showing respectively the following criteria: in the experience phase 89% of the students were in very good, reflection 75% in regular, conceptualization 54% in the good indicator as well as application with 61%. It can be concluded that the students were initially at a low level of learning in the different phases of the ERCA cycle, and subsequently, after the application of the pedagogical proposal, they improved significantly in the phases of experience, reflection, conceptualization and application, which shows that the use of Kolb's cycle in physical education classes improves the teaching process and therefore the learning process in students. Keywords: ERCA, Teaching-learning, teaching methods, physical education